The Impact of Gadget Use on Language Development in Young Children - Andita Purnama Dewi; Wili Astuti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of digital technology has integrated gadgets into the lives of young children, creating a paradox in their impact on language development. These devices have the potential to be effective educational tools as well as obstacles to development, depending entirely on how they are used. This study aims to analyse in depth the dual impact (positive and negative) of gadget use on the language development of children aged 3-6 years, in an Islamic educational setting as well as to explore the mediating role of parents and teachers. This study uses a descriptive qualitative approach conducted at the PAUD Aisyiyah in Sukoharjo Regency. The research subjects consisted of children, parents/guardians, classroom teachers, and the school principal, who were selected purposively. Data were collected through participant observation, semi-structured interviews, and document studies, then analysed using Miles and Huberman's interactive model. The findings revealed that the impact of gadgets is dualistic and highly determined by the quality of adult mediation and the content accessed. Guided use with educational content (such as Nussa Rara and Cocomelon) contributed to an increase in vocabulary, pronunciation of Islamic phrases, and confidence in storytelling. Conversely, unsupervised exposure to age-inappropriate content (such as Anomali animations) resulted in delayed speech, inappropriate code-mixing, and imitation of coarse language. This study concludes that gadgets are essentially neutral tools. Their impact on early childhood language development is determined by the digital ecology surrounding the child, which includes content quality, duration of use, and-most importantly-the quality of mediation from parents and teachers. Synergistic collaboration between home and school environments in building digital literacy and applying consistent boundaries is essential to ensure that technology functions as a means of language enrichment, not as an obstacle to development.